Energy and the way we live : a Courses by Newspaper reader - Kranzberg, Melvin; Hall, Timothy A; Scheiber, Jane L.; Courses by Newspaper (Project) (San Francisco : Boyd & Fraser Pub. Co., 1980)
Bibliography: p. 471-491.